Sosialisasi Kelayakan Air Sumur Sebagai Pencuci Beras di Pemukiman TPA Sumur Batu di Kecamatan Bantar Gebang - Flora Elvistia Firdaus (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
The Sumur Batu landfill uses open dumping in managing its waste, where waste was piled up in an open space and over time the volume continues to increase. Residents who live around the landfill will have positive and negative implications, waste becomes a source of problems and waste brings sustenance. Based on the data collected 60% have a job as a garbage scavenger, of which 40% have other livelihoods. The existence of the landfill results in a decrease in the quality of well water, where water is an essential need for washing rice, drinking, and bathing. The water characterization was identified as colored, and oily. This community service was carried out employing outreach techniques with a participatory approach, to find out the acceptance of residents to their well water. To obtain quantitative data, a semi-structured questionnaire was distributed which was conducted by purposive random sampling on respondents who live in the area around the Sumur Batu landfill. Optimizing the tabulation of the highest response questionnaire data obtained was R² = 0.8976. The results of the analysis identified that 66.67-93.4% of the respondents were aware that the well water used was not suitable for daily needs.